2023
DOI: 10.1021/acs.inorgchem.2c03587
|View full text |Cite
|
Sign up to set email alerts
|

Anion-Directed Self-Assembly of Calix[4]arene-Based Silver(I) Coordination Polymers and Photocatalytic Degradation of Organic Pollutants

Abstract: Coordination polymers (CPs) have recently emerged as promising candidates for heterogeneous photocatalysis due to their structural designability and tunable properties. Herein, we developed two novel Ag­(I)-calix[4]­arene coordination polymers with the formula {[Ag2(μ-NO3)L1 ]} n (CP 1) and {[AgL1 ]·PF6} n (CP 2) (L1 = 2-mercapto-5-methyl-1,3,4-thiadiazole resorcinol calix[4]­arene). Crystallography revealed that anion coordination and self-inclusion behavior induced the cavitand and silver ions to self-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…Under the synergistic systems, Rhb was completely degraded within 90 min, while MO was completely degraded within 150 min and 210 min, respectively. After reviewing the literature summaries for comparison, it was found that the photocatalyst in this study is comparatively simple to prepare and can be mass produced [ 54 , 55 , 56 , 57 , 58 , 59 ]. With synergistic photocatalysis, 100% of the dye can be degraded in a relatively short time, as shown in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Under the synergistic systems, Rhb was completely degraded within 90 min, while MO was completely degraded within 150 min and 210 min, respectively. After reviewing the literature summaries for comparison, it was found that the photocatalyst in this study is comparatively simple to prepare and can be mass produced [ 54 , 55 , 56 , 57 , 58 , 59 ]. With synergistic photocatalysis, 100% of the dye can be degraded in a relatively short time, as shown in Table 3 .…”
Section: Resultsmentioning
confidence: 99%